Full Orifice Patching without Annuloplasty for Severe Functional Tricuspid Valve Regurgitation - Calafiore, Antonio Maria; De Filippo, Carlo Maria; Totaro, Antonio; Pelini, Piero; Mauro, Michele Di (The Thoracic and Cardiovascular Surgeon, 2018)
Surgical treatment of severe functional tricuspid regurgitation associated with dilated right ventricle and increased chordal tethering (>8 mm) is challenging. We designed a technique where the anterior and posterior leaflets are detached from 50% of the annulus and a patch as large as the tricuspid orifice is sewn to augment the leaflets' tissue to force the coaptation with the septal leaflet. Annuloplasty is not performed, as it can only increase the chordal tethering, reducing the benefit of tissue augmentation. Early and midterm results in a subgroup of patients with unfavorable anatomical aspects are encouraging.
Keywords: tricuspid valve; echocardiography (all modalities, applications); tricuspid surgery